2019
DOI: 10.1111/jcmm.14475
|View full text |Cite
|
Sign up to set email alerts
|

MAGE genes: Prognostic indicators in AL amyloidosis patients

Abstract: A high frequency of MAGE‐CT (cancer testis) antigens are expressed in Multiple Myeloma (MM) patients; however, in other plasma cell dyscrasias, their potential function remains unclear. We measured the expression of MAGE‐CT genes (MAGE‐C1/CT7, MAGE‐A3, MAGE‐C2/CT10) in 105 newly diagnosed amyloid light‐chain (AL) amyloidosis patients between June 2013 and January 2018 at Peking University People's Hospital using real‐time quantitative polymerase chain reaction. In the newly diagnosed AL patients, the positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…MAGE family members have attracted increasing attention as biomarkers in cancer and as immunotherapy targets. In total, >40 human proteins are considered CTAs, and these are mainly locally expressed in testis tissues, and partly expressed in ovarian and placental tissues ( 4 ). MAGE proteins are normal tissue antigens that exist in testicular cells, serve an important role in the early stages of spermatogenesis and are abnormally highly expressed in cancer types that may be immunogenic ( 5 ).…”
Section: Mage Family and Its Encoded Proteinsmentioning
confidence: 99%
“…MAGE family members have attracted increasing attention as biomarkers in cancer and as immunotherapy targets. In total, >40 human proteins are considered CTAs, and these are mainly locally expressed in testis tissues, and partly expressed in ovarian and placental tissues ( 4 ). MAGE proteins are normal tissue antigens that exist in testicular cells, serve an important role in the early stages of spermatogenesis and are abnormally highly expressed in cancer types that may be immunogenic ( 5 ).…”
Section: Mage Family and Its Encoded Proteinsmentioning
confidence: 99%
“…Many studies have suggested that CTAs may represent valuable targets for the development of anti-cancer therapies with limited side effects [3][4][5]. Melanoma-associated genes (MAGEs) are CTAs expressed in various malignancies and have been widely studied as prognostic biomarkers [6][7][8][9]. Expression of the CTA MAGE-A3 correlates with aggressive clinical progression and drug resistance in variety of carcinomas, such as non-small cell lung carcinoma, diffuse large B-cell lymphoma, and gastric cancer [10][11][12].…”
Section: Introductionmentioning
confidence: 99%